2021
DOI: 10.1186/s12885-021-08605-x
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis and indirect treatment comparison of modified FOLFIRINOX and gemcitabine plus nab-paclitaxel as first-line chemotherapy in advanced pancreatic cancer

Abstract: Background Modified FOLFIRINOX and gemcitabine plus nab-paclitaxel (GEM-NAB) have been recommended as first-line therapies for advanced pancreatic cancer (PC). Due to the lack of evidence to directly compare them, we conducted this network meta-analysis to indirectly compare the effectiveness and toxicity of modified FOLFIRINOX and GEM-NAB. Methods The eligible retrospective studies on treatments related to modified FOLFIRINOX and GEM-NAB up to 4 A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
0
7
1
Order By: Relevance
“…Several retrospective studies have found that there is no significant difference between the two chemotherapy regimens [8][9][10]. Moreover, a network meta-analysis including twenty-two studies in 2021 reported that the survival and toxicity of these two chemotherapy regimens were similar in advanced pancreatic cancer [11]. However, a retrospective study in Korea concluded that FFX would be a better first-line treatment choice than AG as FFX achieved a longer overall survival in metastatic pancreatic cancer [12].…”
Section: Introductionmentioning
confidence: 99%
“…Several retrospective studies have found that there is no significant difference between the two chemotherapy regimens [8][9][10]. Moreover, a network meta-analysis including twenty-two studies in 2021 reported that the survival and toxicity of these two chemotherapy regimens were similar in advanced pancreatic cancer [11]. However, a retrospective study in Korea concluded that FFX would be a better first-line treatment choice than AG as FFX achieved a longer overall survival in metastatic pancreatic cancer [12].…”
Section: Introductionmentioning
confidence: 99%
“…2023;14(5):325-339 studies have shown that FFX is likely to be associated with a longer OS when compared to GnP [17,18,27,28,38]. There was no statistical difference found with a longer PFS with the use of FFX or GnP but pooling of studies and a larger number of participants from previous meta-analysis showed that FFX was associated with a longer PFS in contrast to GnP [10]. Safety profiles have differed between the two regimens with a difference of results in multiple studies.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, the previous studies did not evaluate the detailed safety profiles for the two regimens; hence, our meta-analysis, with a larger sample size and excellent statistical power, examined the safety profiles and included the most recent published studies. Importantly, the literature search period for our study extends until February 2023; therefore, our study encompasses recently published randomized controlled trials (RCTs), which were conducted to fill in the literature gap [10]. Lastly, our study has different clinical implications based on patient settings.…”
Section: Introductionmentioning
confidence: 99%
“…Although the differences between OS and PFS for both regimens are statistically insignificant, NPXL+GMC has been shown to be more effective, with indications of less toxicity. [8][9][10] Unfortunately, pancreatic cancer is a chemoresistant disease. This is due to acquired abnormalities in the tumor cell membrane transport protein hENT1, 11 nucleoside enzymes 12,13 and changes in the epithelial-mesenchymal transition.…”
Section: Discussionmentioning
confidence: 99%